Dehydrated guava by-product in feed for slow-growing broilers - Vieira, Silvia Silva; Tavares, Fernando Barbosa; Vieira, Ernilde Dos Santos; Moura, Eslane da Silva; Lopes, Wanderson dos Santos; Marinho, Andressa Martins; Reis, Cassio Pinho dos; Galvão, Luckas Thiago Oliveira; Neta, Ernestina Ribeiro dos Santos (Frontiers in Animal Science, 2023)
This study evaluated the use of dehydrated guava by-products (DGBP) in the feed of slow-growing broilers as a substitute for corn. A total of 324 one-day-old broiler Naked Neck from a slow-growing lineage were used. At 30 days of age, the broilers were distributed in an entirely randomized experimental design consisting of four treatments with nine replicates and nine birds in each replicate. The treatments were differentiated by varying concentrations of DGBP (0, 5, 10, and 15%) in the feed. Performance data [feed intake, weight gain, and feed conversion ratio (FCR)] were evaluated from 30 to 60 days and 61 to 84 days of age. At 84 days of age, the broilers were slaughtered; subsequently, the analyses of carcass and organ yield in terms of chemical composition of the breast, thigh and drumstick, and meat quality parameters (coloration, pH, weight loss by cooking and dripping, shear force, and sensory evaluation) were performed. There was no effect of DGBP on the average weight, weight gain, feed consumption, and FCR of the broilers (P > 0.05). However, there was an increasing linear effect (P < 0.05) on the gizzard yield and a quadratic effect on the liver and abdominal fat yield, where treatments with 5 and 10% DGBP obtained the highest yield percentages. There was no effect (P > 0.05) of DGBP addition on chemical composition, pH, shear force, and weight loss by cooking and dripping. A linear increasing effect on coloration (P < 0.05) was found due to dietary DGBP in all the cuts of meat. In addition, a significant difference (p < 0.05) was found in the texture of the breast meat, where the greater the amount of DGBP added, the greater the scores attributed by the tasters. In conclusion, DGBP can be included up to 15% in the diet of slow-growing broilers without altering the production performances, carcass and cut yield, and meat quality parameters. Furthermore, it promoted a reddish coloration of the breast skin and thigh skin of the birds.